AD 381 : heretics, pagans and the Christian state - Freeman, Charles, 1947- (Pimlico, 2009)
In AD 381, Theodosius, emperor of the eastern Roman empire, issued a decree in which all his subjects were required to subscribe to a belief in the Trinity of the Father, Son and Holy Spirit. This edict defined Christian orthodoxy and brought to an end a lively and wide-ranging debate about the nature of the Godhead; all other interpretations were now declared heretical.